Surgery versus Expectant Management in Patients with Endometrioma who Seek Pregnancy. Issue 3 (July 2017) - Muzii, Ludovico; Di Tucci, Chiara; Di Feliciantonio, Mara; D'Amelio, Renzo; Rech, Francesco; Panici, Pierluigi Benedetti
Ovarian endometriomas are a common finding in both infertile and non-infertile women. For non-infertile women planning to seek pregnancy in the presence of an ovarian endometrioma, expectant management is a reasonable option, since reassuring data on spontaneous pregnancy rates for non-infertile patient cohorts have been reported. In case of infertile patients, on the other hand, spontaneous pregnancy rates without treatment are disappointing, and surgery, assisted reproductive technology (ART), or a combination of the two, may be suggested. Surgery should be the preferred approach in case of associated pain. Spontaneous pregnancy rates of over 50% have been reported after surgery in infertile patients. If pregnancy does not occur after 12 months, or earlier for older age groups, patients may be referred to ART. Clinical decisions in the scenario of infertility-associated endometriosis are difficult, since many issues have not been properly addressed in randomized clinical trials. The treatment decision should therefore be based on a sound clinical evaluation, tailored to each patient, after careful consideration of various parameters, such as age and ovarian reserve of the patient, previous treatments for the disease, the presence of associated pain, and associated infertility factors.